(untitled) (Research, Society and Development, 2023)
Objective: to identify the educational technologies used in sexual health education with adolescents. Method: this is an integrative literature review study, conducted between May and June 2021, in databases, libraries and academic search engine, with the following descriptors: "Health Education", "Educational Technology", "Sexual Health", "Adolescent" using the Boolean "and". Results: 72 studies were found and with the use of the eligibility criteria 62 articles were discarded, leaving 10 articles. The technologies found with the searches were educational games, multimedia and social networks, tools that demonstrate effective with respect to improving the gain of knowledge about sexually transmitted infections, teen pregnancy, condom use and sexuality. Conclusion: the technologies commonly used in health education with adolescents are educational games, multimedia and social networks, environments considered effective in the learning process of various topics.